Validity evidence for simulator-based obstetric ultrasound competency assessment tool: a multi-center study - Zhao, Yongfeng; Zhou, Ping; Zhu, Wenhui; Xiao, Jidong; Liu, Wengang; Luo, Yingchun; Zhang, Junhui; Yang, Lan; Xu, Yan; Tang, Xiaohong (Ultraschall in der Medizin - European Journal of Ultrasound, 2023)
Purpose To collect validity evidence for a simulator-based obstetric ultrasound competency assessment tool (OUCAT).Methods 89 sonographers from three centers (XY, MC, DT), including novices (n=21), experienced trainees (n=44), and experts (n=24), participated in the competency assessment. Validity evidence of OUCAT was collected according to Standards for Educational and Psychological Testing. Content validity was ensured by reviewing guidelines and reaching expert consensus. The response process was ensured via training raters. Internal structure was explored through internal consistency, inter-rater reliability, and test-retest reliability. Relations to other variables were explored by comparing OUCAT scores of sonographers with different experience. Evidence for consequences was collected by determining the pass/fail level.Results OUCAT included 123 items, of which 117 items could effectively distinguish novices from experts (P<0.05). The internal consistency was represented by the Cronbach’s α coefficient (0.978). The inter-rater reliability was high, with XY being 0.868, MC being 0.877, and DT being 0.937 (P<0.001). Test-retest reliability was 0.732 (P=0.001). The performance of experts was significantly better than experienced trainees, and the performance of experienced trainees was significantly better than novices (70.3±10.7 vs. 39.8±15.0 vs. 20.5±10.6, P<0.001). The pass/fail level determined by contrast group method was 45 points. The passing rate of novices, experienced trainees and experts was 0% (0/21), 31.8% (14/44), and 100% (24/24), respectively.Conclusion Simulator-based OUCAT exhibits good reliability and validity in assessing obstetric ultrasound skills.
Keywords: obstetric ultrasound; competency; assessment; simulation; validity